The explosion of real time and the structural conditions of temporality in a society of control: durations and urgencies of academic research. Issue 6 (2nd November 2017) - Lapping, Claudia
ABSTRACT: In the context of ongoing debates about the distinctive temporalities associated with contemporary regulative regimes, this paper explores the interpretive trajectories initiated in contrasting conceptualisations of the politics of time. This exploration is developed through analysis of interview data from a study of unconscious relations in academic practice. Section one uses one moment of data to contrast phenomenological, Deleuzian and Lacanian theorisations of the relation between time and subjectivity. Section two is an exegesis of Lacan's paper on Logical Time. This outlines the way temporality is structured in relation to the subject's guess about the expectations of the Other. Section three uses this to develop an interpretation of three temporalities that constitute the space of contemporary academic subjectivities. The final section considers the intensification of the juxtaposition of these incongruent temporalities, contrasting Lacanian and Deleuzian theorisations of time in the Real/virtual and their implications for both methodological and political strategy.